A comprehensive assessment framework for Mykad / Nik Azmi Nik Omar - Nik Omar, Nik Azmi (Institute of Graduate Studies, UiTM, 2012)
We have witnessed a quantum leap in information communication technology (ICT). It is now pervasive with our everyday life and this has resulted in recent development of many new applications using ICT. Governments and Private Sectors have capitalized on this technological advancement in a variety of applications. Essentially technology is applied to increase efficiency and effectiveness. In some business entities, it can be used as a competitive advantage. The Malaysian government too has applied technology to gain the benefit and one of these is using multi-application smartcard which included personal identification. This is followed by other governments from various countries that launched a multipurpose identification smartcard. However, at the same time, being in the forefront has its own shortfall especially in the area of ensuring that smartcard is protected from any security breach.